2009
DOI: 10.1007/s11116-009-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of bicycle route choice preferences in Texas, US

Abstract: In the U.S., the rise in motorized vehicle travel has contributed to serious societal, environmental, economic, and public health problems. These problems have increased the interest in encouraging non-motorized modes of travel (walking and bicycling). The current study contributes toward this objective by identifying and evaluating the importance of attributes influencing bicyclists' route choice preferences. Specifically, the paper examines a comprehensive set of attributes that influence bicycle route choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(199 citation statements)
references
References 23 publications
11
178
1
9
Order By: Relevance
“…Immigrant status positively influences (log) commute distance, as it has been observed that immigrants have longer commutes than do nonimmigrants (see Paleti et al, 2013). Further, individuals with young children are less likely to travel by non-motorized modes and more likely to travel by motorized vehicles (as they undertake pick up/drop off activities; see Sener et al, 2009). Also, in the simulation design, we specify the number of young active adults in the individual's household to negatively influence travel by motorized vehicles, as households with millenials tend to undertake their out-of-home activities less using private vehicles (see Bhat et al, 2014a).…”
Section: Non-nominal Equation System With Exogenous and Latent Constrmentioning
confidence: 99%
“…Immigrant status positively influences (log) commute distance, as it has been observed that immigrants have longer commutes than do nonimmigrants (see Paleti et al, 2013). Further, individuals with young children are less likely to travel by non-motorized modes and more likely to travel by motorized vehicles (as they undertake pick up/drop off activities; see Sener et al, 2009). Also, in the simulation design, we specify the number of young active adults in the individual's household to negatively influence travel by motorized vehicles, as households with millenials tend to undertake their out-of-home activities less using private vehicles (see Bhat et al, 2014a).…”
Section: Non-nominal Equation System With Exogenous and Latent Constrmentioning
confidence: 99%
“…Stated preference methods include surveys or focus groups where participant cyclists are presented with different route segment characteristics (e.g., speed limit, traffic volume, and presence of bicycle facilities) and are asked about their preferences for each [46][47][48][49]. Some studies include hypothetical scenarios, such as biking to work or an all-day meeting [25,50].…”
Section: Bicycle Route Choice Studiesmentioning
confidence: 99%
“…Dill et al (2007) identified that the perception about availability of comfortable bicycle facilities is a strong factor affecting bicycle ridership and bicycle mode share (Dill & Voros, 2007). Other studies that collected information from surveys found that weather conditions, route conditions, interaction with motorized traffic, street parking, and characteristics of bicycle facilities have an impact on the motivation to bicycle (Winters, Davidson, Kao, & Teschke, 2011) (Sener, Eluru, & Bhat, 2009). …”
Section: Cyclists' Comfortmentioning
confidence: 99%
“…The findings suggest that bike lane presence, crossing traffic volume, speed limit, speed parking, traffic signals, and crossing distance affect levels of service and comfort at intersections (Carter, Hunter, Zegeer , & Stewart, 2007) (Landis, Vattikuti, Ottenberg, Petritsh, Guttenplan, & Crider). In terms of the route, bicycle paths separated from traffic have been found to be preferred by users (Garder, Leden, & Pulkkinen, 1998) (Sener, Eluru, & Bhat, 2009) (Winters, Davidson, Kao, & Teschke, 2011). Models utilizing data from a smartphone app (ORcycle) that focuses on measuring comfort levels also show that traffic and commercial vehicles are the most important factors that decrease cyclists' comfort levels.…”
Section: Data Collection I: Multiple Subjectsmentioning
confidence: 99%